Approaches to Scaffolding in Teaching Mathematics in English with Primary School Students in Colombia - Heidy Selene Robles Noriega; Ximena Patricia Corzo Zambrano (Universidad de La Sabana, 2011)
Teaching mathematics in a second-language (L2) environment requires teachers to understand both relevant mathematics concepts and the L2. Teachers must be aware that the explanations, clarifications, and development of mathematical language require that students have sufficient competence in the L2 to understand what is being taught. This implies teaching language to students in three specific ways, as suggested by Coyle, Hood, and Marsh (2010): language of learning, language for learning, and language through learning. Teaching mathematics also requires teachers to apply different types of scaffolding. This study seeks to identify the types of scaffolding and instructions used by the mathematics teacher at a bilingual school in Santa Marta, Colombia teaching first-grade students in English. Classroom observations, as well as interviews and classroom observation checklists, were carried out to determine what the mathematics teacher was already doing in the classroom in terms of scaffolding. The resultant data suggests that a range of visual aids and careful use of the L1 can play significant role in supporting the simultaneous development of content and linguistics competences.